Softness Perception Interfered by Friction in Gliding Virtual Surfaces - Hongbo Wang; Shogo Okamoto (IEEE Access)
Recent studies have shown that surface friction affects softness perception when objects are slid over using fingers. This study examines whether this phenomenon extends to interactions with virtual objects using a stylus-based haptic interface, which independently controls friction and object stiffness. In Experiment 1, we investigated how kinematic friction coefficients influence perceived stiffness. Results showed that surfaces with minimal friction (coefficient =0) were perceived as stiffer than those with higher friction ( $≥ 0.2$ ). For instance, a surface with a stiffness of 500 N/m at minimal friction was perceived as equivalent to 581.7 N/m at a friction coefficient of 0.4. However, the perceived stiffness was not different under frictional conditions, with coefficients ranging from 0.2 to 0.6. Experiment 2 evaluated participants’ ability to discriminate stiffness levels (400 N/m vs. 500 N/m and 500 N/m vs. 600 N/m) under three friction conditions (0, 0.25, and 0.5). Discrimination accuracy declined with increasing friction. These findings provide valuable insights for designing haptic interfaces and virtual reality applications, enabling developers to optimize user experiences by accounting for the interplay between friction and perceived softness.